Reverse engineering : an industrial perspective (Berlin ; London : Springer, 2010)
A collection of essays from world-leading academic and industrial authors that yields insight into various aspects of reverse engineering.
To Reverse Engineering.- Methodologies and Techniques for Reverse Engineering-The Potential for Automation with 3-D Laser Scanners.- Reverse Engineering-Hardware and Software.- Selecting a Reverse Engineering System.- to Rapid Prototyping.- Relationship Between Reverse Engineering and Rapid Prototyping.- Reverse Engineering in the Automotive Industry.- Reverse Engineering in the Aerospace Industry.- Reverse Engineering in the Medical Device Industry.- Legal Aspects of Reverse Engineering.- Barriers to Adopting Reverse Engineering.
Keywords: Reverse engineering